Drug Utilization Evaluation of Two Broad-Spectrum Antimicrobials: Cefepime and Piperacillin/Tazobactam in a Teaching Hospital in Tabriz, Iran - Parviz Saleh; Hadi Hamishekar; Farnaz Naeimzadeh; Sara Mikaili; Hamid Owaysee Osquee; Haleh Rezaee (Research Center for Rational Use of Drugs (RCRUD), 2019)
Background: The inappropriate use of antibiotic leads to microbial resistance, nosocomial infections and increased hospital costs. The broad-spectrum antibiotics, such as cefepime and piperacillin/tazobactam play an important role in the empiric therapy of serious infections. Methods: Demographic data, duration of prescription, dose, dosage adjustment in renal impairment and accompanied prescribed antibiotics were extracted from medical files. UpToDate and AHFS drug information 2012 were considered as standards of rational prescribing. Data analysis was performed by SPSS 18 software. Results: Drug dosage and indication were appropriate in 16 (23%). The most common antibiotic administered with cefepime was ciprofloxacin (37 cases). In 21 patients, cefepime dosage should have been adjusted according to renal impairment, whereas it has done only in 16 (22.9%) patients. Culture was done in 60 (85.8%) cases. Culture ordered before starting of antibiotics took place in 3(4.2%) patients. In 22(31.4%) patients, the result of culture was negative. Drug dosage and indication were appropriate in 34 (48%). The most common antibiotic administered with tazocin was vancomycin (45 cases). In 9 patients, tazocin dosage should have been adjusted according to renal impairment and it has done. Culture was done in 53 (75.8%) cases. Culture ordered before starting of antibiotics took place in 6(8.57%) patients. In 9(12.8%) patients, the result of culture was negative. Conclusion: The results showed that there was an injudicious use of cefepime and piperacillin/tazobactam at Sina hospital, evidenced by the significant number of inappropriate empiric prescriptions and inappropriate drug modifications, based on the results of microbial cultures and antibiograms.